2007
DOI: 10.1631/jzus.2007.b0296
|View full text |Cite
|
Sign up to set email alerts
|

Pressure from the lips and the tongue in children with class III malocclusion

Abstract: Abstract:Objective: To discuss possible relationships between class III malocclusion and perioral forces by measuring the pressure from the lips and the tongue of children with class III malocclusion. Methods: Thirty-one children with class III malocclusion were investigated and their perioral forces were measured at rest and during swallowing under natural head position by a custom-made miniperioral force computer measuring system. Results: The resting pressures exerted on the labial side and palatine side of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 15 publications
4
19
4
Order By: Relevance
“…This finding was similar to that of the previous study of Ruan et al (2007). This suggested that the maximum lip closing force of Class III patients is weaker in both adults and children.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding was similar to that of the previous study of Ruan et al (2007). This suggested that the maximum lip closing force of Class III patients is weaker in both adults and children.…”
Section: Discussionsupporting
confidence: 92%
“…Lambrechts et al (2010) found that the maximum lip pressure in Class II division 1 was lower than that in Class I, but there were no significant differences in the other comparisons (Class I, Class II division 1, Class II division 2 and Class III). Ruan et al (2007) showed that paediatric patients (4e6 years old) with a Class III malocclusion generated lower perioral muscle forces. This may cause less bone apposition in this area, which aggravates the clinical features of Class III malocclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,14,15 Posen 15 found that the subjects with bimaxillary protrusion had low lip strength, compared with Class I and Class II Division 2 patients, using a device for measuring the strength of the lips. Ruan et al 20 reported that patients aged 4 to 6 years with Class III malocclusion had lower perioral forces and this muscle hypofunction might be secondary to the spatial relation of the jaws.…”
Section: Introductionmentioning
confidence: 99%
“…When using this instrument, great attention should be given to controlling the action of compensatory muscles, such as the mentalis. Other assessing instruments reported in the literature use force or pressure lip sensors attached to the teeth (Gentil and Tournier 1998;McHenry et al 1999;Ruan et al 2007). These electrodes are fixed by special glues or dental adhesive.…”
Section: Resultsmentioning
confidence: 99%